Study on an ETC solar water heater using flat and wavy diffuse reflectors. (2021) - Dinesh, S.N.; Ravi, S.; Manoj Kumar, P.; Subbiah, Ram; Karthick, Alagar; Saravanakumar, P.T.; Aravinth Pranav, R.
Abstract: In recent days, evacuated tube (ETC) solar water heating systems are proposed to be the prominent solution for the residential as well as industrial water heating needs of various capacities, without depending on the electrical grids. They serve hot water economically, and independently. However, the efficiency of the water heater is a main concern, especially on the days having low solar insolation and on rainy days. In addition, the underneath of the evacuated tubes is usually not exposed to the direct sunlight and become inactive, which further diminishes the performance of these water heaters. Hence, it is the hot topic of research to improve the performance of these water heaters with the aid special arrangements. In this paper, an experimental assessment is presented to improve the performance of the evacuated tube solar water heater using two different forms of diffuse reflectors, namely flat diffuse reflector (FDR) and wavy diffuse reflector (WDR). The results evidenced that the use of diffuse reflectors enhanced the tank water temperature during the day time, significantly. Further, it was discerned that the tank water temperature was enhanced by 4 °C and 6 °C respectively, with the aid of flat diffuse reflector and wavy diffuse reflector. Comparatively, the wavy diffuse reflector improved the water temperature by 2 °C higher than the flat diffuse reflector.